PREVALENCE AND ASSOCIATED RISK FACTORS OF RENAL COMPLICATIONS IN CONGENITAL CARDIAC DISEASE PATIENTS - Khalil, Hafsa; Ahmed, Iftikhar; Saleem, Kamal; Younas, Umair; Iftikhar, Rawail; Khan, Adeela (Pakistan Armed Forces Medical Journal, 2018)
Objective: To investigate the risk factors associated with renal complications and comparison of peritoneal dialysis survival and non-survival patients after open heart surgery.Study Design: Descriptive cross-sectional study.Place and Duration of Study: Pediatric cardiac anesthesia Department of Armed Forced Institute of Cardiology & National Institute of Heart Diseases from Jul 2017 to Jan 2018.Material and Methods: Retrospective data was collected from hospital based registry. Demographics, clinical characteristics, complications and outcome of patients were recorded. Data analysis of 199 patients was done on SPSS version 22.Results: Total of 199 patients were enrolled in the study, mean age was 4.9 ± 5 years (p=0.01), 117 (59.1%) were male and 82 (40.9%) were female patients. Out of total, 24 (12%) patients had kidney disease (KD) and underwent peritoneal dialysis (PD). Sixteen children (66.7%) died after PD while 08 children (33.3%) survived after PD. 09 (37.5%) had pulmonary edema (p